2013
DOI: 10.5812/ircmj.2160
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kangaroo Mother Care (KMC) on Breast Feeding at the Time of NICU Discharge

Abstract: BackgroundExclusive breastfeeding is one of the most important essential components of Kangaroo Mother Care.ObjectiveThis study was performed to evaluate the effects of KMC on exclusive breastfeeding just at the time of discharge.Patients and MethodsIn this cross sectional study, 251 consecutive premature newborns admitted to neonatal intensive care unit (NICU) between May 2008 and May 2009 in Alzahra University Hospital in Tabriz were evaluated. All of candidate mothers were educated for KMC method by schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 25 publications
3
33
1
7
Order By: Relevance
“…This is in contrast with findings in other studies describing KC as having positive effects on the performance and duration of breastfeeding [20,43,44]. This difference in outcome might be explained by the fact that other studies used quantitative methods to measure the breastfeeding performance.…”
contrasting
confidence: 95%
“…This is in contrast with findings in other studies describing KC as having positive effects on the performance and duration of breastfeeding [20,43,44]. This difference in outcome might be explained by the fact that other studies used quantitative methods to measure the breastfeeding performance.…”
contrasting
confidence: 95%
“…From the onset this program consists of two major parts; eating and sleeping. When the infant wakes on mother's chest, the breasts are near and very little work is required to get to them and feed (Heidarzadeh et al 2013). Caruna (2008 believes that once the infant has fed it will go to sleep and it is only when the infant is on the mother's body will this sleep be the right quality for brain wiring.…”
Section: What Makes Skin To Skin Contact the Basis For Breastfeeding?mentioning
confidence: 99%
“…Similar significance was found in other study. [20][21][22][23][24] In this study, 35% had health problems in cases and 65 % in control with significant difference. Similarly, nearly 45% of the infants had health problems in a study conducted by Lakew W et al 25 50% of infants had respiratory distress with oxygen requirement among case group and 40% in control.…”
Section: Discussionmentioning
confidence: 74%
“…In another study, though similar non significance was found by Swarnakar K et al, (Case -11.49+1.7, Control-12.59+2.63) and RP Suman et al, (Case -12.78±6.27 and control -12.86±5.77), the duration of stay was found to be less. 20,23,24 90% were exclusively breast fed in cases and 72% in control, with significant difference between the groups. Similar significance was found in other study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation